Sequencing of disease-modifying therapies for relapsing–remitting multiple sclerosis: a theoretical approach to optimizing treatment. (3rd August 2018) - Grand'Maison, Francois; Yeung, Michael; Morrow, Sarah A.; Lee, Liesly; Emond, Francois; Ward, Brian J.; Laneuville, Pierre; Schecter, Robyn
Abstract: Multiple sclerosis (MS) is a chronic disease which usually begins in young adulthood and is a lifelong condition. Individuals with MS experience physical and cognitive disability resulting from inflammation and demyelination in the central nervous system. Over the past decade, several disease-modifying therapies (DMTs) have been approved for the management of relapsing–remitting MS (RRMS), which is the most prevalent phenotype. The chronic nature of the disease and the multiple treatment options make benefit–risk-based sequencing of therapy essential to ensure optimal care. The efficacy and short- and long-term risks of treatment differ for each DMT due to their different mechanism of action on the immune system. While transitioning between DMTs, in addition to immune system effects, factors such as age, disease duration and severity, disability status, monitoring requirements, preference for the route of administration, and family planning play an important role. Determining a treatment strategy is therefore challenging as it requires careful consideration of the differences in efficacy, safety and tolerability, while at the same time minimizing risks of immune modulation. In this review, we discuss a sequencing approach for treating RRMS, with importance given to the long-term risks and individual preference when devising a treatment plan. Evidence-based strategies to counter breakthrough disease are also addressed.